Kecerdasan Spiritual Santri Melalui Puasa - Agus Ali; Nurwadjah Ahmad EQ; Andewi Suhartini (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to determine the spiritual intelligence of students through fasting. This type of research is qualitative. The approach chosen by the author is phenomenology. Determination of data sources in this study according to the information obtained in the form of words and documents that are presented and described as they are and examined in order to find meaning. The researcher acts directly as an instrument and as a data collector from the results of observations, interviews and documentation. The results of this study are students who carry out Ramadan fasting at the Ummul Quro Al-Islami Islamic boarding school feel a different spiritual spirit from the previous months. Santri are more enthusiastic in reading the Qur'an, more enthusiastic in praying in congregation, getting up at night for tahajjud prayer, sharing food sincerely, especially when breaking the fast, patiently waiting for the Maghrib call to prayer, feeling supervised by Allah in fasting so that they are more honest with themselves. and there are still many positive values ​​that are felt. As for some of the wisdom of fasting as follows; fasting makes a person able to gain degrees of piety, fasting increases faith, fasting can train one's sincerity, fasting gives peace of mind, fasting trains a person to always feel the presence of Allah, fasting trains patience, fasting educates someone to have high social empathy, fasting educates someone to have a soul big, and fasting trains honesty.